Circulating Th22 and Th9 Levels in Patients with Acute Coronary Syndrome - Ying-zhong Lin; Bang-wei Wu; Zheng-de Lu; Ying Huang; Ying Shi; Hao Liu; Ling Liu; Qiu-tang Zeng; Xiang Wang; Qing-wei Ji (Mediators of Inflammation)
Background. CD4+ T helper (Th) cells play critical roles in the development and progression of atherosclerosis and the onset of acute coronary syndromes (ACS, including acute myocardial infarction (AMI) and unstable angina pectoris (UAP)). In addition to Th1, Th2, and Th17 cells, Th22 and Th9 subsets have been identified in humans. In the present study, we investigated whether Th22 cells and Th9 cells are involved in the onset of ACS. Methods. The frequencies of Th22 and Th9 cells were detected using a flow cytometric analysis and their related cytokine and transcription factor were measured in the AMI, UAP, stable angina pectoris (SAP), and control groups. Results. The results revealed a significant increase in the peripheral Th22 number, AHR expression, and IL-22 levels in patients with ACS compared with those in the SAP and control groups. Although there was no difference in the peripheral Th9 number among the four groups, the PU.1 expression and IL-9 levels were significantly increased in patients with ACS compared with the SAP and control groups. Conclusions. Circulating Th22 and Th9 type responses may play a potential role in the onset of ACS symptom.